HUBUNGAN PERILAKU MASYARAKAT DALAM PEMBERANTASAN SARANG NYAMUK DAN FAKTOR LINGKUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI WILAYAH PUSKESMAS I DENPASAR SELATAN DAN PUSKESMAS I DENPASAR TIMUR - Dwi Jata; Nyoman Adi Putra; I.B.G. Pujaastawa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Dengue hemorrhagic fever (DHF) is one of diseases that causes health problems in Indonesia and oftenly creates extraordinary events with great death. The purpose of this research is to discover relationship community behavior in mosquito nesting eradication and environmental factors with DHF incidence in 1st Public Health Center Denpasar Selatan and 1st Public Health Center Denpasar Timur. The research design used is observational, cross-sectional. Total sample of 82 households. Sampling was done in proportion sampling method. Results of the analysis of environmental variables associated with DHF incidence in 1st Public Health Center Denpasar Selatan: occupant density (p = 0.02), mobility (p = 0.01), the habit of hanging clothes (p = 0.04). 1st Public Health Center Denpasar Timur: mobility (p = 0.00), clogged water ditches (p = 0.00), containers water existance (p = 0.03), the habit of hanging clothes (p = 0.00). Knowledge, attitude and actions in 1st Public Health Center Denpasar Selatan and 1st Public Health Center Denpasar Timur statistically correlated with DHF incidence. As conclusion of the research results, in 1st Public Health Center Denpasar Selatan and 1st Public Health Center Denpasar Timur, that is mobility, the habit of hanging clothes, knowledge, attitude and actions strongly related with DHF incidence, while that is clogged water ditches, containers water existance and occupant density has no relation with DHF incidence. Public Health Center need to intensify health promotion, improves the quality of MNE (PSN), and the Provincial Health Service need to support Public Health Center on setting policies which necessary.